The Labor-saving Kitchen: Sources for Designs of the Architects’ Small Home Service Bureau - Tucker, Lisa M. (Enquiry The ARCC Journal for Architectural Research, 2014)
The history of the kitchen has received much attention from designers and design historians. Since the writings of Catharine Beecher, designers, household engineers, and others have written about the importance of the kitchen as the center of the home. This research traces the impact of the writings of theorists such as Frederick Taylor, Georgie Boynton Child, Helen Binkerd Young, and Christine Frederick on the designs produced by the architects in the first quarter of the 20th century. Frederick’s work took the concept of an efficient kitchen to a new level applying movement studies and introducing new ideas to the kitchen layout and arrangement. In a properly laid out and equipped kitchen, steps were saved by placing kitchen cabinets, ovens and stoves, refrigerators and sinks where they were needed in the sequence of food preparation and delivery to dining table as well as clean up after the meal. In her books, she also provided advice on a variety of considerations, such as appliances and accessories, lighting and ventilation; materials, finishes and color; and appliances and equipment. In 1919 a group of architects dedicated to improving the housing stock in the United States through good design banded together to form the Architects’ Small House Service Bureau (ASHSB). Their first plan book, How to Plan Finance and Build your Home published in 1921, also encouraged labor-saving kitchen design and provided advice on kitchen design. The research reported here assesses how the influence of Frederick and Boyton’s advice as reflected in the work of and interpreted by Helen Binkerd Young is demonstrated in the kitchen designs of the ASHSB’s first plan book. A plan content analysis instrument, developed using Frederick’s writings and edited to include other variables from Young and Child, is used to analyze the 99 kitchens and two essays in the ASHSB’s plan book. The plans and accompanying comments evidence enthusiasm for the concept of scientific management and other labor- and energy-saving concepts promoted by Frederick. Many of her specific suggestions are incorporated in their kitchen designs, but there is limited evidence that ASHSB designs are only influenced by Frederick but rather include other popular labor-saving concepts of the early 20th century.